„WASHING HEAD HOUSING” 3D PRINTING FROM FA 100 DRILLING INSTALLATION, USING PETG FILAMENT - Sorin Alexandru FICĂ; Claudiu BABIȘ; Andrei DIMITRESCU (Fiabilitate şi Durabilitate)
In this work, we proposed 3D printing additive manufacturing, using Fused Deposition Modeling technology for the washing head housing, which is common for water drilling installations FA100, FA125, FH150 and FG40. Due to the common use of this washing head for the water drilling installations FA100, FA125, FH150 and FG40, we use the generic name "FA100 Washing Head". We use 3D printing technology because, on the one hand, it is technically possible to make the part and on the other hand, for economic reasons. It is approximately ten times cheaper to make the part through 3D printing than through conventional technologies